A Dichotomy of Processes of Structural Change in The Economic System - Piotr WALĄG (Communications of International Proceedings, 2020)
The occurrence of premature deindustrialisation processes in the employment category would point to a large part of the surplus agricultural labour force that will either remain trapped in this sector or be shifted to low-productivity industries in the informal sector and informal services. The aim of this work is to show whether the stylized facts of the Polish economy (as an example of a catching up economy) in the years 1995-2018 allow us to state that in the structural changes to the economic system in that period we were dealing with a dual course of deindustrialisation processes. There is also a hypothesis that the Polish economy is experiencing a dual course of deindustrialisation processes, which may be the main reason for the persistence of over-employment in agriculture (hidden unemployment) and high employment in low-productivity processing industries in the informal sector and in informal services. The dual course of the processes of structural changes is the main reason for the persistence of a very high unemployment rate in the Polish economy between 1995 and 2015, at an average of 15.5%, and for the emergence and persistence of hidden unemployment in agriculture between 11% and 13% in the whole of the period 1995-2018.
Keywords: Deindustrialisation; Production Structure; Employment Structure; Sustainable Economic Growth; Full Employment.